User Guide to the G+ Customer Profile Tool (G+ CP) - Orr, A.; Polar, Vivian; Ashby, Jacqueline A. (International Potato Center, 2021)
The G+ Customer Profile is a tool for identifying and describing target customers (users) of a breeding product, such as crop varieties and breeds of livestock. The use of this tool highlights gender differences among customers or users to ensure that they are considered when target customer segments are defined. This tool helps a breeding program to prioritize its customers (e.g. how many they are, their geographical distribution and their socio-economic situation, besides their preferences for certain traits in a breeding product). Knowing how women’s preferences differ from those of men (and why) helps to breed products that encourage gender equity. This tool is designed for public sector breeding, which lacks the feedback that is built into the breeding programs of private companies. The tool helps to segment users (e.g. women smallholders), to decide which ones to serve (target) and to address their agricultural breeding needs. The G+ Customer Profile should be developed with the G+ Product Profile. The G+ Customer Profile shows how the three stages of segmenting, targeting and profiling each target customer segment can be covered in six clearly defined steps: 1. Make a product map. 2. Make a customer map. 3. Make the evidence table. 4. Target customer segment(s). 5. Identify product preferences, and 6. Craft a G+ Customer Profile.